Biological inhibition of soil nitrification by forest tree species affects Nitrobacter populations. (5th January 2020) - Laffite, Amandine; Florio, Alessandro; Andrianarisoa, Kasaina Sitraka; Creuze des Chatelliers, Charline; Schloter‐Hai, Brigitte; Ndaw, Sidy M.; Periot, Charlotte; Schloter, Michael; Zeller, Bernd; Poly, Franck; Le Roux, Xavier
Summary: Some temperate tree species are associated with very low soil nitrification rates, with important implications for forest N dynamics, presumably due to their potential for biological nitrification inhibition (BNI). However, evidence for BNI in forest ecosystems is scarce so far and the nitrifier groups controlled by BNI‐tree species have not been identified. Here, we evaluated how some tree species can control soil nitrification by providing direct evidence of BNI and identifying the nitrifier group(s) affected. First, by comparing 28 year‐old monocultures of several tree species, we showed that nitrification rates correlated strongly with the abundance of the nitrite oxidizers Nitrobacter (50‐ to 1000‐fold changes between tree monocultures) and only weakly with the abundance of ammonia oxidizing archaea (AOA). Second, using reciprocal transplantation of soil cores between low and high nitrification stands, we demonstrated that nitrification changed 16 months after transplantation and was correlated with changes in the abundance of Nitrobacter, not AOA. Third, extracts of litter or soil collected from the low nitrification stands of Picea abies and Abies nordmanniana inhibited the growth of Nitrobacter hamburgensis X14. Our results provide for the first time direct evidence of BNI by tree species directly affecting the abundance of Nitrobacter .